Morphological and Genetic Variation in Three Populations of Hoplobatrachus tigerinus from Bangladesh - Hasan, M; Khan, MMR; Sumida, M (Progressive Agriculture, 2013)
In order to investigate the morphological and genetic variation of Indian bullfrog Hoplobatrachus tigerinus, live samples were collected from three populations located in Khulna (southern part), Char Nilokhia and Netrokona (central part) in Bangladesh. The proportions of head length and head width (HL : HW), eye length and tympanum diameter (EL:TD), head length and snout length (HL : SL), internarial space and interorbital distance (IN:IOD) and internarial space and distance from nostril to tip of snout (IN:NS) of the Khulna population were significantly higher (p<0.05) than those of the other two populations. For allozyme study, 4 enzymes were screened, where 5 presumptive scorable loci were identified. The highest values of mean proportion of polymorphic loci (<0.95), mean number of alleles per locus and mean number of heterozygous loci per individual were observed in the Khulna population (60%, 1.60 and 14.0% respectively). The pairwise genetic differentiation (FST and Neis D) was the highest (0.279 and 0.157, respectively) between the Khulna and Netrokona populations. The UPGMA dendrogram showed two clusters i.e. the Char Nilokhia and Netrokona populations formed one cluster, whereas the Khulna population alone made another cluster. These results suggested that the Khulna population diverged morphologically and genetically from the other two populations probably due to its geographical distance. Further extensive study will be necessary for elucidating the whole aspects of differentiation in H. tigerinus from Bangladesh. DOI: http://dx.doi.org/10.3329/pa.v19i2.16954 Progress. Agric. 19(2): 139 - 149, 2008